Comparative Gross Anatomical Studies on the Humerus of Crested Serpent Eagle (Spilornis cheela) and Brown Wood Owl (Strix leptogrammica) - Keneisenuo, Keneisenuo (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on the comparative gross characteristics of the humerus of crested serpent eagle and brown wood owl. In the proximal extremity, interiorly head of the humerus of crested serpent eagle was thicker as compared to the brown wood owl. A large and deep pneumatic foramen was present on themedial surface of the proximal extremity of the humerus in crested serpent eagle however it was small and shallow in brown wood owl. The lateral surface of the crest of the humerus was sharp in brown wood owl but was blunt in crested serpent eagle. It was concluded that the differences in osteological features of the humerusin both the species may be due to its flying and terrestrial habits.